2020
DOI: 10.3390/jcm9030738
|View full text |Cite
|
Sign up to set email alerts
|

High Levels of Kinesiophobia at Discharge from the Hospital May Negatively Affect the Short-Term Functional Outcome of Patients Who Have Undergone Knee Replacement Surgery

Abstract: Background: Kinesiophobia is a psycho-cognitive factor that hampers recovery after orthopedic surgery. No evidence exists on the influence of kinesiophobia on the short-term recovery of function in patients with knee replacement (KR). Therefore, the aim of the present study is to investigate the impact of kinesiophobia on short-term patient-reported outcomes (PROMs) and performance-based measures (PBMs). Methods: Forty-three KR patients filled in the Tampa scale for kinesiophobia (TSK) at time of discharge. Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 54 publications
0
15
0
Order By: Relevance
“…In patients with fibromyalgia, 75.1% reported “maximum” kinesiophobia [ 8 ]. Moreover, 55.8% of patients undergoing knee replacement surgery presented high values of kinesiophobia [ 10 ]. Further, patients with a high degree of hallux valgus (HV) deformity showed increased levels of kinesiophobia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In patients with fibromyalgia, 75.1% reported “maximum” kinesiophobia [ 8 ]. Moreover, 55.8% of patients undergoing knee replacement surgery presented high values of kinesiophobia [ 10 ]. Further, patients with a high degree of hallux valgus (HV) deformity showed increased levels of kinesiophobia.…”
Section: Discussionmentioning
confidence: 99%
“…Various authors have reported a relationship between kinesiophobia and general psychological problems as a common feature in subjects with hallux valgus deformities [ 9 ], cardiovascular pathology [ 3 ], fibromyalgia syndrome [ 8 ], lupus erythematosus [ 7 ], knee replacement [ 10 ], a reconstructed anterior cruciate ligament [ 6 ], chronic fatigue syndrome [ 11 ], as well as chronic back and musculoskeletal pain [ 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that CNP individuals may be difficult or incapable of performing functional tasks [ 15 , 16 ]. Also, kinesiophobia can further hinder their overall functional performance, which can affect their quality of life [ 17 , 18 ]. Due to the avoidance of physical exercise, kinesiophobia may contribute to a deterioration of functional ability, leading to decreased mobility and chronic pain [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Also, kinesiophobia can further hinder their overall functional performance, which can affect their quality of life [ 17 , 18 ]. Due to the avoidance of physical exercise, kinesiophobia may contribute to a deterioration of functional ability, leading to decreased mobility and chronic pain [ 18 ]. However, there is no conclusive evidence, how kinesiophobia impacts functional performance among individuals with CNP.…”
Section: Introductionmentioning
confidence: 99%
“…In its final stage, knee arthroplasty is usually needed to restore function and reduce pain [ 2 ]. However, over 20% of the patients who undergo this intervention report dissatisfaction with surgery results after three years [ 3 ], related to high pain scores and low functional scores [ 4 ], which usually produce kinesiophobia and avoidance behaviors [ 5 ]. Patients who undergo total knee replacement (TKR) usually report pain as the biggest barrier to recovering their usual activity [ 4 ].…”
Section: Introductionmentioning
confidence: 99%